2018
DOI: 10.1039/c7cp08243f
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a silver salt on the nanostructure of a Au(111)/ionic liquid interface: an atomic force microscopy study and theoretical concepts

Abstract: Ionic liquids (ILs) form a multilayered structure at the solid/electrolyte interface, and the addition of solutes can alter it. For this purpose, we have investigated the influence of the silver bis(trifluoromethylsulfonyl)amide (AgTFSA) concentration in 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)amide ([Py]TFSA) on the layering using in situ atomic force microscopy. AFM investigations revealed that the Au(111)/electrolyte interface indeed depends on the concentration of the salt where a typical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 38 publications
(91 citation statements)
references
References 61 publications
4
87
0
Order By: Relevance
“…(23), considering eqs. (16) and (18), and dividing by I. We find that Z is the sum of three distinct contributions…”
Section: Impedancementioning
confidence: 92%
“…(23), considering eqs. (16) and (18), and dividing by I. We find that Z is the sum of three distinct contributions…”
Section: Impedancementioning
confidence: 92%
“…Eventually, at concentrations above 500 µM AgTFSA, the ordered structure collapses into a simple double layer. The developed thermodynamic continuum model, which treats the ionic liquid as being composed of hard spheres, could be successfully applied to describe the interfacial structure under the influence of Ag additives and to simulate the force-separation curves [119]. To summarize the investigations of metal additives in different ionic liquids, it can be concluded that, in general, the structured interface layer becomes distorted at high metal concentrations; however, at low and intermediate concentrations, a complex interplay with the metallic species and ionic liquid takes place such that each specific combination of additives and liquids must be considered independently.…”
Section: Addition Of Metallic Solvatesmentioning
confidence: 99%
“…The interfacial nanostructures were demonstrated to link to electrochemical performance of an IL/metal anode systems 21,22,23 ; the IL cation and anion chemistry was also found to have a dramatic effect on interfacial layering near the electrode surface 9,10,21,24,25 . The effect of salt concentration on interfacial nanostructures was also considered but with a focus on low to moderate salt concentration range 26,27,28 . From several recent studies 29,30,31,32 , we know that dendrite free metal anode cycling is possible in so-called 'superconcentrated' IL electrolytes (e.g.…”
mentioning
confidence: 99%